A novel, all-dielectric, microwave plasma generator towards development of plasma metamaterials. (4th October 2016) - Cohick, Zane; Luo, Wei; Perini, Steven; Baker, Amanda; Wolfe, Douglas; Lanagan, Michael
Abstract: A proof of concept for a microwave microplasma generator that consists of a halved dielectric resonator is presented. The generator functions via leaking electric fields of the resonant modes — TE01δ and HEM12δ modes are explored. Computational results illustrate the electric fields, whereas the stability of resonance and coupling are studied experimentally. Finally, a working device is presented. This generator promises potentially wireless and low-loss operation. This device may find relevance in plasma metamaterials; each resonator may generate the plasma structures necessary to manipulate electromagnetic radiation. In particular, the all-dielectric nature of the generator will allow low-loss interaction with high-frequency (GHz–THz) waves.